Non-Steroidal Anti-inflammatory Drugs As Host-Directed Therapy for Tuberculosis: A Systematic Review - Kroesen, Vera M.; Gröschel, Matthias I.; Martinson, Neil; Zumla, Alimuddin; Maeurer, Markus; van der Werf, Tjip S.; Vilaplana, Cristina (Frontiers in Immunology, 2017)
Lengthy, antimicrobial therapy targeting the pathogen is the mainstay of conventional tuberculosis treatment, complicated by emerging drug resistances. Host-Directed Therapies, including Non-steroidal anti-inflammatory drugs (NSAIDS), in contrast, target host factors to mitigate disease severity. In the present Systematic Review, we investigate whether NSAIDS display any effects as therapy of TB and discuss possible mechanisms of action of NSAIDS as adjunctive therapy of TB. Ten studies, seven pre-clinical studies in mice and three clinical trials, were included and systematically reviewed. Our results point towards a beneficial effect of NSAIDS as adjunct to current TB therapy regimens, mediated by decreased lung pathology balancing host-immune reaction. The determination of the best timing for their administration in order to obtain the potential beneficial effects needs further investigation. Even if the pre-clinical evidence requires clinical evaluation, NSAIDS might represent a potential safe, simple, and cheap improvement in therapy of TB.